1994
DOI: 10.1212/wnl.44.10.1907
|View full text |Cite
|
Sign up to set email alerts
|

Morning reduction of cerebral vasomotor reactivity

Abstract: We measured cerebral vasomotor reactivity during normoventilation, hyperventilation (hypocapnia), and breathing of 6% CO2 (hypercapnia) in 20 normal subjects during the hours of 6 to 8 AM, 1 to 3 PM, and 7 to 9 PM. Cerebral vasomotor reactivity was calculated, using transcranial Doppler, as percent change in the mean blood flow velocity of the middle cerebral artery per mm Hg change in end-tidal CO2 during hypocapnia and hypercapnia. Vasomotor reactivity during hypercapnia was lower in the morning (1.72 +/- 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
2
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 0 publications
1
39
2
2
Order By: Relevance
“…In contrast, over the same time period, morning hypercapnic cerebral vascular reactivity is markedly reduced, a finding that is in agreement with others. 1,16 The similarity in the magnitude of the hypoxic cerebral vascular response between the evening and morning is noteworthy, because we have previously reported that this response is absent during NREM sleep 7 ; indeed, hypoxia is associated with a reduction in CBF during NREM sleep. 7 Although the mechanism responsible for the abolition of this response is unknown, the present data would suggest that, in the majority of individuals, the return of the hypoxic response on waking occurs rapidly.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In contrast, over the same time period, morning hypercapnic cerebral vascular reactivity is markedly reduced, a finding that is in agreement with others. 1,16 The similarity in the magnitude of the hypoxic cerebral vascular response between the evening and morning is noteworthy, because we have previously reported that this response is absent during NREM sleep 7 ; indeed, hypoxia is associated with a reduction in CBF during NREM sleep. 7 Although the mechanism responsible for the abolition of this response is unknown, the present data would suggest that, in the majority of individuals, the return of the hypoxic response on waking occurs rapidly.…”
Section: Discussionmentioning
confidence: 72%
“…1,18,28 Research suggests that the incidence of stroke is highest during the morning hours, especially on awakening, 30,31 a finding that has been attributed to a reduction in cerebral vascular reactivity. 1 An intact CBF response to IH, during this time period, could be interpreted as a protective mechanism, acting to maintain CBF during any hypoxic episode such as that reported in patients with OSA. It remains to be established if the present observations, in healthy young males, can be extrapolated to "at-risk" groups such as the elderly or those with OSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 -28 It exhibits diurnal variations, reaching low points during morning hours when stroke events are most prevalent. 29 Both symptomatic and asymptomatic carotid artery stenosis are well-known contributors to impaired cVMR, 30 with vasomotor response to CO 2 lower on the stenotic side and improving after carotid endarterectomy. 27 Previous investigations report that impaired cVMR predicts higher stroke risk, 8,9,31 although one recent study suggests basal MCA-BFV is more important to stroke risk than cVMR.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] A large number of publications have focused on identifying the underlying pathophysiological mechanisms and have reported rhythmic variation in blood pressure, vascular tone, platelet function, blood viscosity, fibrinolysis, cerebral vasomotor activity, and concentrations of hormones and coagulation factors to be of relevance in this context. [3][4][5][6][7][8][9][10][11][12][13] Furthermore, time-of-day-dependent variations in neuronal vulnerability to cerebral ischemia may also provide an explanation for temporal differences in stroke onset. 14,15 Most of these rhythms are governed by the circadian clock, which generates an endogenous rhythm via clock genes that interact in transcriptional/translational feedback loops.…”
mentioning
confidence: 99%